Adiposity and chronic kidney disease: observations from UK Biobank - Zhu, P (2020)
Background: Excess adiposity is associated with increased risk of chronic kidney disease (CKD). However, the relative contribution of central and general adiposity to CKD risk and the underlying mechanism of mediation are unknown.